Vermicomposto e trichodermacomo bioproduto no desenvolvimento inicial de tomate - Santos, Willian Braga dos (2019)
Tomatoes (Solanum lycopersicum) are one of the most consumed oleracea in the world. Brazil is responsible for 3% of world production. However, it is, basically, to supply the domestic market. This crop demands great phytosanitary care, and even receives the application of agrochemicals. This fact, besides causing higher costs, can also be harmful to the ecosystem. To reduce the application of chemical products in the production systems, fungi of the Trichoderma genus have been demonstrated a protective activity in the roots of the plants against pathogens in the soil. In addition, they have the potential to promote initial growth when in adequate doses for the crop. Seen as a way to treat organic waste effectively and quickly vermicomposting promote the stabilization of organic materials, which can also be used as a substrate for seedling production. Therefore, the objective of this work was to test a bioformulate based on Trichoderma ssp. and different percentages of vermicomposting in early tomato development. The treatments consisted of different doses of a bioformulate based on Trichoderma ssp. (Majestic®) associated or not with different percentages of vermicompost applied in the modality of seed treatment. The experiment was cultivated on two substrates: Germitest Paper and Biomix® Commercial Substrate. The evaluations were emergency velocity index, dry mass of root and aerial part, aerial part length, root volume, and germination. The results obtained were that the use of Majestic® had a positive effect on the early development of tomatoes plants. There was an interaction between the different doses of vermicompost and the bioformulate. The 10 times of the recommended doses of Majestic® showed the highest average for the analyzed attributes the non-application of vermicompost responded more positively in this research. In higher doses of Majestic® the treatments that received some percentage of vermicompost showed an increase in the averages for the attributes studied. We conclude that in order to have a beneficial interaction between plant and microorganism in the efficiency of use of Majestic®, it depends not only on the dose used, but also on the type of substrate used.